Characterization of the self-assembly of New Jersey polyomavirus VP1 into virus-like particles and the virus seroprevalence in Japan - Zhou, Xianfeng (Sci Rep, 2019)
New Jersey polyomavirus (NJPyV) was discovered in 2014 in a pancreatic transplant recipient’s vascular endothelial cells. Here, in the recombinant baculovirus system, VP1 protein of NJPyV expressed in insect cells was processed. The protein self-assembled into virus-like particles (NJPyV-LPs) in a cell-type-dependent manner, and the particles were then released into the culture media. Spherical ~50-nm-dia. NJPyV-LPs of uniform size with morphology resembling that of the native particles of polyomaviruses were purified from the fraction at 1.33 g/cm(3) in supernatants of VP1-expressing Sf9 cells. We investigated the antigenic properties of purified NJPyV-LPs and performed a VLP-based enzyme immunoassay to determine the age-specific prevalence of NJPyV infection in a general Japanese population aged 1–70 years. The overall seropositivity rate of anti-NJPyV antibodies was only 1.8%. This might be explained by the low circulation of NJPyV in Japan. This is the first report of a large-scale serological survey of NJPyV in Asia (n = 1,050).